Female Obesity: An Emerging Threat in Sri Lanka. (29th May 2020) - Jayasinghe, Imasha; Hettiarachchi, Ayesh; Koralegedara, Iresha; Amarasinghe, Gayani; Agampodi, Thilini; Dissanayake, Kumara; Warnasekara, Janith; Wickramasinghe, Nuwan; Abeyrathne, Parami; Agampodi, Suneth
Abstract: Objectives: Emerging body of evidence clearly shows a transgenerational effect of obesity. The maternal health programme in low- and middle-income countries are typically focusing on undernutrition, while the burden of overweight and obesity are mostly overlooked. The objective of this study was to evaluate the burden of malnutrition in a cohort of pregnant mothers in Sri Lanka. Methods: A cross sectional analysis was conducted as a part of an ongoing cohort of all pregnant women registered in the public health system and having a period of gestation less than 12 weeks in Anuradhapura district, Sri Lanka were recruited over three months period during 2019. Clinical and anthropometric assessments were done in 240 dedicated clinics. Results: Total of 3190 mothers were recruited with full anthropometric profile with mean age of 28.3 years (SD 5.6). Prevalence of overweight, obesity grade I, II and III according to Asian cut off limits were 15.3% (n = 520), 31.4%(n = 1065), 1.5% (n = 51) and 2% (n = 7) respectively. Prevalence of underweight was only 15.9%. Waist circumference >80 cm was reported among 1189 (35%) mothers. A marked spatial distribution of obesity was observed with ranging from 23% to 46%. As a more important and unbiased factor in the first trimester of pregnancy, we looked at the predictors of WC >80. After the adjustment for POA and age, living environment variables indicating higher level of financial status such as using electricity as main cooking fuel (OR 2.276), having a wooden floor (OR 1.688), floor tiles (OR 1.377), three-wheeler (OR 1.22) or other vehicle ownership (OR 1.287) were associated with central obesity. Higher education level of women and lower educational level of husband were also identified as predictors. Women from moor ethnic group were also at a higher risk compared to others. Conclusions: Context specific strategies are required to tackle the double burden of malnutrition and the observed gross micro geographical variation in obesity needs further studies. Funding Sources: Accelerating Higher Education Expansion And Development (AHEAD) Operation.